Effect of Filter Aids on Two Different Filter Media Under High Filtering Velocities - Nurnadia Andenan; Mohd Rashid; Siti Hajar; Nor Ruwaida Jamian; Khairunnisa Mohd Pa’ad; Ammar Mohd Rashid (Chemical Engineering Transactions, 2019)
A fabric filter is an excellent air pollution control device for fine particles emissions control due to its high collection efficiency. The problem associated with fabric filter is that it has a short life span due to wear and tear connected with the operating conditions of the system. Treatment of fabric filter using filter aids is one of the simplest techniques to overcome this problem. In this study, the effect of filtration aids known as PrekotAC, onto two different types of filter media i.e PTFE and ryton under high filtering velocity was carried out in a laboratory scale filtration system. This formulated filter aids PrekotAC material which consists of activated carbon and PreKot™, served as a two in one filter aids material (adsorbent and pre-coating material) that helps to overcome the wear and tear problem as well as control the emission of sub-micron pollutants in air pollution control. The effect of the various combinations of filtration aids on pressure drop, particle penetration and permeability across the two-filter media under different filtration velocities was investigated. Results showed that ryton presents a lower pressure drop under various combinations of PrekotAC for different filtration velocities compared to PTFE. A lower pressure drop across the fabric filter resulted a higher permeability property of ryton which allows higher volumetric air flow rates passing through it compared to PTFE filter. The study suggests that the addition of PreKotTM in the formulation of PrekotAC significantly affect both pressure drop and permeability of the filter media. The study also showed that the total particle penetration through the filter media is highly influenced by the filtration velocity. It was found that the total particle penetration through PrekotAC 10 : 90 (wt% basis of PreKotTM:activated carbon) was the lowest while the highest was PrekotAC 40 : 60 of the four formulated PrekotAC admixtures. In addition, the total particles penetrating through the filter media was the highest for the highest filtering velocity of 8 m/min for all cases.